The Ideal of Holiness in Hildegard of Bingen (1098-1179) - Giannacco, Valentina (De Medio Aevo, 2020)
This paper deals with the ideal of holiness in Hildegard of Bingen, which comes to light both from the two hagiographies written for Disibod and Rupert, the heavenly patrons of her two monasteries, and from the Symphonia armoniae celestium revelationum, a cycle of poems in which the author examines all the ecclesiastical history from its apostolical origins up to the birth of monasticism. The Virgin Mary as the Mother of God has an essential role in the Symphonia. She reconnects the Creation of the world with the “regeneration” of the world, which occurred in the day of Incarnation. Three different levels of the interpretation of the Book of Genesis flow into her womb and in Christ: the creation (literal level), the Church (allegorical level) and the monasticism (moral-tropological level). Disibod and Rupert represent the moral level. They are indeed the symbol of the rise of the human being in the path of the virtues, which has the reunification with Christ as the destination.
Keywords: The Virgin Mary; St. Disibod; Heavenly Jerusalem; coenobium; ornatus mundi